The Factors for Motivational and Emotional Context of Educational Process at Medical High School - A.Ye. Abaturov; Ye.A. Agafonova; V.L. Babich; Ye.L. Krivusha; G.S. Kaniuka (Zaslavsky O.Yu., 2015)
The aim of the study is improvement of education quality on the basis of improvement of teacher and student interaction. Methods. Quality evaluation of teaching of a lecture course and practical lessons has been done on the basis of questionnaire survey among the students. Results. The survey was conducted anonymously, in small groups (8-10 people) among 4th-year students, trained at the Department of pediatrics 1 and medical genetics. One hundred and eighty seven respondents took part in the research under discussion, among them 151 domestic and 36 foreign students. There were studied the subjective perception of students about adequacy of presentation and importance of the lecture material, organizational aspects of a practical lesson, the role of additional teaching material in the educational process, professional orientation, correct behavior of teachers. The opinion of the students about the obtained knowledge and participation in educational process were almost identical. The level of satisfaction with knowledge and skills acquired during the lectures and practical lessons reached 89.8 % and 92.4 % correspondingly among domestic and 85.6 % and 93.8 % among foreign students.